Patients' priorities around drug-resistant tuberculosis treatment: A multi-national qualitative study from Mongolia, South Africa and Georgia - Annabelle South; Parveen Dhesi; Conor D. Tweed; Bazarragchaa Tsogt; Suzanne Staples; Nestani Tukvadze; Gantsetseg Dorj; Sindisiwe Zaca; Ekaterine Sanikidze; Nasanjargal Purev; Hanif Esmail; Rochelle Burgess (Taylor & Francis Group, 2023)
We conducted qualitative research exploring the treatment experience of people with DR-TB. We held nine focus group discussions with 57 adults undergoing/recently completed treatment for DR-TB in Georgia, Mongolia and South Africa. Translated transcripts were analysed using thematic analysis. We identified three higher order themes: (1) Treatment experience and the role of good relationships with healthcare providers: Treatment duration, pill burden and side-effects were challenging aspects of treatment. Side-effects/symptoms that were visible signs of illness were particularly troubling. Good relations with clinical staff helped combat fear and uncertainty regarding treatment. (2) Mental distress and opportunities for wellbeing: The shame, stigma and isolation people experienced as a result of their DR-TB diagnosis was an important cause of mental distress. No longer being infectious enabled people to resume work and socialising. Positive emotions emerged with good treatment outcomes. (3) Fear and worry along the treatment journey: Participants expressed fears about TB: infecting others; whether they would be able to endure treatment; side-effects; health consequences of treatment. Worries mostly disappeared with successful treatment. Alongside measuring side-effects, time to culture conversion and cure rates, future trials of DR-TB treatments should capture how quickly visible symptoms resolve, quality of life measures, and mental health outcomes.